2014
DOI: 10.1016/j.paid.2014.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and personality in classical, jazz and folk musicians

Abstract: HighlightsCreativity and personality of classical, jazz, and folk musicians was compared.Jazz musicians show higher divergent thinking ability.Jazz musicians accomplish more creative musical activities and achievements.Classical musicians show a high amount of practice and win more competitions.Folk musicians are more extraverted and publish more musical productions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 22 publications
9
57
0
11
Order By: Relevance
“…The findings are in line with current understanding of the attentional demands of creative idea generation and insight, which propose that inhibition of certain regions, particularly in the left hemisphere, allow for "remoter" associates to be selected, as opposed to more local ones [36,43,44]. Increased alpha activity may therefore be the mechanism by which improvisational jazz musicians perform better on DT tasks than musicians from classical and folk genres [52], as performing jazz music tends to require internally-oriented attention to continuously generate and evaluate musical ideas [53]. The extent to which improvisational training can create long-term, and perhaps domain-general improvements in creativity, is worthy of exploration.…”
Section: Creativity As Remote Associationssupporting
confidence: 83%
“…The findings are in line with current understanding of the attentional demands of creative idea generation and insight, which propose that inhibition of certain regions, particularly in the left hemisphere, allow for "remoter" associates to be selected, as opposed to more local ones [36,43,44]. Increased alpha activity may therefore be the mechanism by which improvisational jazz musicians perform better on DT tasks than musicians from classical and folk genres [52], as performing jazz music tends to require internally-oriented attention to continuously generate and evaluate musical ideas [53]. The extent to which improvisational training can create long-term, and perhaps domain-general improvements in creativity, is worthy of exploration.…”
Section: Creativity As Remote Associationssupporting
confidence: 83%
“…But divergent thinking also predicted improvisation scores, even after controlling for practice hours. The results of this study and other recent work (e.g., Benedek et al, 2014a;Lewis and Lovatt, 2013) point to a potential overlap between the ability to generate creative ideas in general and the ability of jazz musicians to generate novel musical sequences. Pressing (1988) conceptualized improvisation as the interaction between higher-order referent processes and long-term memory.…”
Section: Improvisation and Domain-general Processessupporting
confidence: 62%
“…Musical specialization may also be related to cognitive abilities. Benedek and coworkers thus report that jazz musicians score higher than classical musicians on test of divergent thinking . Other studies have, for example, found percussionists to outperform nonpercussionist musicians on timing tasks .…”
Section: Discussionmentioning
confidence: 97%
“…Benedek and coworkers thus report that jazz musicians score higher than classical musicians on test of divergent thinking. 33 Other studies have, for example, found percussionists to outperform nonpercussionist musicians on timing tasks. 34 This suggests that differences in the relative strengths of different musical aptitudes (melody, rhythm, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation